Demography Population of Sumatran Surili (Presbytis melalophos ssp. mitrata Eschsholtz, 1821) and The Diversity of Vegetation as Their Habitat in Riparian Site of Geopark Mengkarang Purba, Merangin Regency - Asrizal Paiman; Novriyanti Novriyanti; Cory Wulan (Media Konservasi, 2018)
Surili Sumatera (Presbytis melalophos ssp. mitrata Eschsholtz, 1821) is a primate species commonly found in Sumatra and Kalimantan. Thesubspecies of mitrata are known to be found along the Batanghari River, to the Geopark Mengkarang Purba area. However, data on the number ofspecies in their habitat in Geopark Mengkarang Purba is not yet available. Thus, research on the demographics of riparian populations in riparianareas and the diversity of tree species as a residential habitat in the region is required. The data of this study were collected for ± 3 months in theMerangin Geopark area, West Bangko district in Bedeng Rejo and Rengas Ulu Villages. Geographically this location is located at 0210'43.9 "LS,102oo10'47,5" BT with wavy topography. All aspects of population demographics were observed with transect strip technique on the 1.000 x 100 meterline for 10 repetitions per day. The number of paths observed was 3 lines representing the sampling intensity of 0,48% of the total area of the studysite. The results showed that the total population of Sumatran Surili found in Geopark Mengkarang Purba area was 29 individuals with sex ratio of1:2 and age structure which was considered progressive for the growth of Surili Sumatera population in Purba Geopark Mengkarang. The level oftree species diversity found in 31 species at the study site is close to high (H '= 2,96), most of which are found as fruit trees useful for the life anddevelopment of the Sumatran surili population.Keywords: demography population, Geopark Merangin, Presbytis, riparian site